Harmonic morphisms from even-dimensional hyperbolic spaces - Svensson, Martin (MATHEMATICA SCANDINAVICA, 2003)
In this paper we give a method for constructing complex valued harmonic morphisms in some pseudo-Riemannian manifolds using a parametrization of isotropic subbundles of the complexified tangent bundle. As a result we construct the first known examples of complex valued harmonic morphisms in real hyperbolic spaces of even dimension not equal to 4 which do not have totally geodesic fibres.